Economic outcomes of gender diverse people: New evidence from linked administrative data in New Zealand - Christopher S. Carpenter; Linda Kirkpatrick; Maxine J. Lee; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2024)
We provide new evidence on the economic outcomes of transgender and gender diverse people in New Zealand (NZ) using confidential linked administrative data from driver license records - which identify gender diverse people since 2021 - linked to NZ birth and tax records. We document that gender diverse people are younger than both transgender and cisgender people but are more highly educated than transgender people. Relative to otherwise similar cisgender men, we find large employment and earnings penalties for transgender and gender diverse people. Earnings gaps for gender diverse individuals are especially large.
Keywords: J1; 330; transgender; gender diverse; employment; earnings; linked administrative data; New Zealand